Wizards of the game - Lubar, David (Puffin, 2004)
Eighth grader Mercer, whose passion is the fantasy role-playing game Wizards of the Warrior World, hopes to use a fund raiser to bring a gaming convention to his middle school, but instead he attracts four genuine wizards who are trapped on Earth and want his help in returning to their own world.